An Investigation of the Relationship between University Students’ Internet Addiction Levels, Social Anxiety, and Communication Skills - Bayzan, Şahin; Aksakalli, Gülşah (Addicta: The Turkish Journal on Addictions, 2024)
Abstract: The aim of this study is to examine the relationship between university students’ Internet addiction levels, communication skills, and social anxiety. The sample for the research is 5660 university students from Turkey. The participants were reached through an easily accessible sampling method. The Addiction Scale, Interpersonal Communication Competence Inventory, and Social Anxiety Scale were used to collect data. A relational survey model was used in the analysis of the data. The prominent result of the research is that the Internet addiction status, communication skills, and social anxiety status of university students show significant differences according to different variables. It was found that there was a low negative relationship between Internet addiction and communication skills, and a moderate positive relationship between Internet addiction and social anxiety among university students. In the model established to predict the Internet addiction of university students through communication skills and social anxiety variables, the social anxiety variable was found to be a statistically significant predictor of Internet addiction.
Keywords: Addiction; anxiety; communication skills; Internet addiction; social anxiety disorder; social interaction